PENGARUH PENGENALAN BAHASA INGGRIS DASAR MELALUI KEGIATAN SOSIALISASI EDUKATIF PADA MINAT BELAJAR MURID DI SD NEGERI 04 PATAMUAN PADANG PARIAMAN - Zahara, Leni; Sidiq, Muhammad Harif; Dewi , Reny Aulia Yosita; Desara, Ammar; Krimadi, Trifona Elisabet; Azmi, Fadillah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effect of basic English language introduction through educational socialization activities on the learning interest of second-grade students at SD Negeri 04 Patamuan, Padang Pariaman. The background of this research is the low interest in learning English among lower-grade students, caused by less engaging teaching methods and minimal stimulation in the school environment. This study employed a descriptive qualitative approach, with data collected through participatory observation and in-depth interviews with teachers, students, and the school principal. The results indicate that educational socialization activities packaged in the form of interactive games, songs, and storytelling successfully increased students' learning interest significantly. Students demonstrated high enthusiasm, increased confidence in speaking, and stronger intrinsic motivation to learn English. This study concludes that the introduction of basic English through fun and contextual educational socialization is proven effective in fostering the learning interest of second-grade elementary school students. This research is expected to serve as a reference for teachers and policymakers in designing English learning programs in elementary schools.